Prevalence of Gastric Ulceration in Horses with Enterolithiasis Compared with Horses with Simple Large Intestinal Obstruction - Valeria Albanese; Amelia Munsterman; Andreas Klohnen (Veterinary Sciences, 2022)
Enterolithiasis is a well-documented cause of colic in horses, especially in some geographic areas such as California and Florida. This retrospective case-control study aims at comparing the prevalence of gastric ulcers in horses affected by enterolithiasis to that in horses affected by other types of large intestinal obstruction. Two hundred and ninety-six horses were included in the study sample. Horses that had surgery for the removal of one or more enteroliths were included in the study as cases. Patients that had surgery for large intestinal simple obstructions other than enterolithiasis (large colon displacement, non-strangulating large colon torsion, and large and small colon impactions) were selected to match case horses for age, sex, and breed and included as controls. A total of 101/148 horses with enteroliths (68%) had gastric ulcers diagnosed during hospitalization, compared with 46/148 of matched controls (31%). There was a significant association between enterolithiasis and gastric ulceration (odds ratio 4.76, p < 0.0001), and a greater prevalence in Thoroughbreds as compared with other breeds (odds ratio 22.6, p < 0.0001). We concluded that enterolithiasis is significantly associated with gastric ulceration (p < 0.0001). The association is stronger in Thoroughbreds.